An evaluation of GMA's News and Public Affairs Library based on users' assessment - Maninang, Leilani P.; Cruz, Ma. Divina P. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
A descriptive survey was used to determine the current procedure/system implemented in the News and Public Affairs Library regarding the storage and retrieval of materials, evaluate it and determine its weakness through user's perception.
The main objective of this study is to evaluate the current procedure/system implemented in the News and Public Affairs Library, find out its weaknesses to help them render better service to their clients through user's perception. It also aims to find out the following: 1) the materials kept in the library; 2) the users of the library and how aware they are of the materials kept in it; 3) how they borrow materials from the library; 4) how long does it take them to get what they want; 5) if they think that there's a faster and better way of doing the job; 6) if the library personnel is efficient; 7) the things that are lacking in their library; 8) if the current procedure/policy implemented in their library is efficient.
In the study made, it was found out that the library needs some rethinking in the implementation of their policies. There are several reasons stated by the users themselves affecting their dissatisfaction like the poor condition of the library, lack of experience and expertise of the library personnel, lack of facilities to use and a clear and strict policy to implement.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: News libraries -- Philippines -- Quezon City